Clinical analysis of 88 patients with chronic radiation-induced rectal injury in a single center from Xinjiang Uygur Autonomous Region - Yiminjiang Tuoheti; Gao Weige; Li Tao; Ma Tenghui (结直肠肛门外科)
[Objectives] To summarize the diagnostic and therapeutic experiences of patients with chronic radiationinduced rectal injury in Xinjiang Uygur autonomous region. [Methods] A retrospective analysis was conducted on the clinical data of 88 patients with radiation-induced rectal injury admitted to the People’s Hospital of Xinjiang Uygur Autonomous Region between January 2019 and October 2024. Patients were classified into four subtypes: telangiectasia (n＝56), ulcerative (n＝17), stenotic (n＝6), and mixed (n＝9). Therapeutic outcomes and follow-up data were analyzed. [Results] Significant differences were observed among the groups in age, body mass index, serum albumin levels, and treatments (P<0.05), while no differences were found in gender, disease duration, comorbidities, hemoglobin levels, or tumor marker positivity (P>0.05). The overall response rate after treatment was 90.9%, with no significant difference in efficacy among subtypes (Z＝3.109, P＝0.375). Among the 88 patients, 23 underwent surgical treatment, including 13 who underwent enterostomy and 10 who received target lesion resection, with abdominal incisions present. Preoperative VAS scores showed no statistical difference between patients undergoing enterostomy and those undergoing target lesion resection (P>0.05). At 2 weeks postoperatively, VAS scores decreased significantly, with lower scores in the target lesion resection group compared to the enterostomy group (P<0.05). Compared with patients who underwent enterostomy, postoperative abdominal incision pain relief was significantly better in the target lesion resection group (Z＝-2.790, P＝0.005). [Conclusion] Chronic radiation-induced rectal injury in Xinjiang Urumqi Autonomous presents as the telangiectasia subtype, with a high overall treatment efficacy. Target lesion resection provided superior postoperative pain relief compared to enterostomy.